Crack initiation and propagation of 30CrMnSiA steel under uniaxial and multiaxial cyclic loading. (May 2019) - Liu, Tianqi; Shi, Xinhong; Zhang, Jianyu; Fei, Binjun
Highlights: Extensive uniaxial and multiaxial fatigue experiments were performed. Stage I crack is affected by stress amplitude ratio and phase angle. Crack propagation life of stage II occupies at least 40% of the total fatigue life. Fatigue failure mechanisms under different shear stress levels are different. Discussions on the non-conservative prediction results by critical plane criteria. Abstract: Effects of stress amplitude ratio and phase angle on crack propagation and fatigue life of 30CrMnSiA steel were discussed by extensive uniaxial and multiaxial fatigue experiments. Crack morphologies were observed by a metallurgical microscope. The crack propagation behavior showed that few cracks of stage I are observed with very low stress amplitude ratios (λ = 0, 0.25). Under the loading conditions with higher stress amplitude ratios (λ ≥ 0.5), the crack length of the stage I increased from about 20 μm to about 50 μm with the increasing of stress amplitude ratio and phase angle. The stage II crack propagated along the maximum normal stress plane, and the propagation life of stage II accounted for more than 40% of the total fatigue life. In addition, through utilizing the replica technique, effects of shear stress level on surface crack morphologies were analyzed. It can be found that fatigue failures are mainly caused by crack propagation under low stress level, while also caused by coalescing of small cracks at the high stress level. Discussions of fatigue life indicated that the stress amplitude ratio affects the fatigue life of the material significantly, while the phase angle has less effect. The prediction results of fatigue life demonstrated that both the McDiarmid criterion and Findley criterion overestimate the multiaxial fatigue life of 30CrMnSiA steel, due to the fact that mechanisms of crack propagation are varied under different loading conditions.